Mozart effect on dental anxiety in 6–12 year old children - Arlette Suzy Setiawan; Hilnia Zidnia; Inne Suherna Sasmita (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2010)
Background: Children anxiety in dental treatment often becomes a barrier for dentist to perform optimum dental treatment procedure. Various methods to manage anxiety and fear in children have been applied including listening to classical music during dental treatment. One of the classical music usually used is music by Mozart. Purpose: This study is aimed to discover the role of classical music by Mozart in dental anxiety changes. Method: This study was a quasi experimental study using purposive sampling method. The samples consist of 30 children between 6-12 years old group who were treated at the Pediatric Dentistry Clinic, Dental Hospital, Faculty of Dentistry Padjadjaran University. The anxiety data was collected using Visual Analogue Scale (VAS) before and after listening on the classical music during treatment. Result: The result of this study showed that there were 23 children (76.67% of subjects) who present decreased anxiety, 7 children (23.33% of subjects) did not present decreased anxiety and none of of subjects showed increased anxiety. Conclusion: It was concluded that listening to music by Mozart during dental treatment can reduce anxiety in 6-12 year old children.Latar belakang: Kecemasan pada anak saat perawatan gigi seringkali merupakan penghalang bagi dokter gigi untuk melaksanakan prosedurperawatan gigi yang optimal. Berbagai metode untuk mengatasi kecemasan dan rasa takutpada anak telah dilakukan termasuk mendengarkan musik klasik selama perawatan gigi. Salah satu musik klasik yang banyak digunakan adalah music oleh Mozart. Tujuan: Penelitian ini ditujukan untuk menemukan peran music klasik Mozart dalam perubahan kecemasan pada perawatan gigi. Metode: Penelitian ini adalah kuasi eksperimental menggunakan metode pengambilan sampel purposif. Sampel terdiri dari 30 anak antara 6-12 tahun yang dirawat di Klinik Kedokteran Gigi Anak, Rumah Sakit Gigi dan Mulut Fakultas Kedokteran Gigi Universitas Padjadjaran. Data kecemasan diambil dengan Visual Analogue Scale (VAS) sebelum dan setelah mendengarkan music klasik selama perawatan. Hasil: Hasil menunjukkan bahwa terdapat 23 anak (76,67% dari subjek) yang menunjukkan penurunan kecemasan, 7 anak (23,33%) tidak menunjukanperubahan kecemasan dan tidak ada (0 anak atau 0%) yang menunjukkanpeningkatan kecemasan. Kesimpulan: Disimpulkan bahwa mendengarkan musik Mozart selama perawatan gigi dapat menurunkan kecemasan di antara anak- anak usia 6-12 tahun.